A case of residual inferior sinus venosus defect after ineffective surgical closure. (3rd October 2014) - Uga, Sayuri; Hidaka, Takayuki; Takasaki, Taiichi; Kihara, Yasuki
Abstract : A 38-year-old woman presented with cyanosis and heart failure 34 years after patch closure of an atrial septal defect and partial anomalous pulmonary venous connection. CT and cardiac catheterisation showed a residual defect that caused right-to-left shunting. The patch almost blocked the inferior vena cava from the right atrium, resulting in uncommon drainage of the inferior vena cava into the left atrium. Other anomalies included the coronary-to-pulmonary artery fistula and duplicate inferior vena cava with dilated azygos venous system. A second surgery was performed, and we confirmed an inferior sinus venosus defect, which is rare and can be misdiagnosed. The ineffective patch closure had caused a haemodynamic status that rarely occurs. We describe the diagnostic process and emphasise the importance of correctly understanding the entity.